ANALYSIS OF PRELIMINARY RESEARCH ON THE PEOPLE OF KARAKALPAK (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
Over the past centuries, many historical researchers have conducted ethnological research on Karakalpaks. In our article, scientists provided valuable information about the ethnological composition of Karakalpaks.